PENGEMBANGAN BAHAN AJAR BERBASIS ARTIFICIAL INTELLIGENCE (AI) UNTUK MENINGKATKAN HASIL BELAJAR MATERI KEBERAGAMAN SOSIAL SISWA KELAS IV SDN OEBOBO 2 KOTA KUPANG - Arnoldus, Angeline; Yulsy Marselina Nitte; Heryon Bernard Mbuik (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid advancement of digital technology has encouraged elementary schools to develop more innovative teaching materials that are able to improve students' learning outcomes. However, the teaching materials used in Pancasila Education learning at SDN Oebobo 2 Kupang City remain dominated by printed textbooks, making students less active and resulting in low learning achievement, particularly on the topic of social diversity. This study aimed to develop Artificial Intelligence (AI)-based teaching materials and determine their feasibility, practicality, and effectiveness in improving fourth-grade students' learning outcomes. The study employed a Research and Development (R&D) approach using the ADDIE development model consisting of Analysis, Design, Development, Implementation, and Evaluation. The research subjects consisted of 46 fourth-grade students divided into an experimental class and a control class. Data were collected through expert validation sheets, teacher and student response questionnaires, and pretest-posttest achievement tests. The developed product was an AI-based interactive learning video integrating ChatGPT, Terabox AI, CapCut, and Mindstamp AI. The results showed that the teaching materials were highly feasible, with media expert validation reaching 77.7%, material expert validation 96.8%, and language expert validation 100%. Teacher and student responses reached 97.5% and 87.5%, respectively, indicating that the product was highly practical. The effectiveness test demonstrated a significant improvement in learning outcomes, with the experimental class average score increasing from 58.82 on the pretest to 80.73 on the posttest. Independent sample t-test analysis showed a significance value of 0.000 (<0.05), while the average N-Gain score reached 0.345, indicating a moderate improvement category. Therefore, AI-based teaching materials are feasible, practical, and effective for improving elementary school students' learning outcomes on social diversity material.